MARKETING STRATEGIES IN KOSOVO INSURANCE COMPANIES - CONCEPTS AND APPROACHES - Stela TODOROVA; Gazmend DEDA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In today's market conditions of living and working, the insurance market is constantly increasing in volume. As a result, competition is very high and the relationship between insurers is constantly changing. The strict approach to increasing insurance profits has shown insurers that they need to abandon the solid base offered to customers. The need for insurance service is constantly growing, so it is imperative that it is constantly improved and adapted to the conditions and needs of customers. For this reason, insurance institutions need to monitor and know what is happening in the insurance market in order to be able to respond in a timely manner to changes in the development of the insurance business. Increasing insurance profits is unthinkable without implementing a marketing strategy. The purpose of this article is to justify the need to develop marketing strategies in agricultural insurance activities in Kosovo. The research is carried out with a qualitative and quantitative method, or with the help of empirical parameters and indicators that the expert literature knows. The main conclusion that the authors make is that insurance is a complex category, as well as a profession. The reason is that it refers not only to the observance of methodological principles, but also to the ideas, enthusiasm and creativity of marketing in providing certain tasks in the field of insurance, especially in the field of agriculture.